2015
DOI: 10.1002/2015jb012047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pore pressure buildup on slowness of rupture propagation

Abstract: Pore fluid pressure is known to play an important role in brittle fracture initiation and propagation, yet the underlying mechanisms remain unclear. We conducted triaxial experiments on saturated porous sandstones to investigate effects of pore pressure buildup on the slowness of shear rupture propagation at different confining pressures. At low to intermediate confinements, rocks fail by brittle faulting, and pore pressure buildup causes a reduction in rock's shear strength but does not induce measurable diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
1
21
0
2
Order By: Relevance
“…22 Inspired by the integral path independent of J integral, 23 the shear fracture energy of sandstone before the peak stress was as follows 22 Inspired by the integral path independent of J integral, 23 the shear fracture energy of sandstone before the peak stress was as follows…”
Section: Shear Fracture Energymentioning
confidence: 99%
“…22 Inspired by the integral path independent of J integral, 23 the shear fracture energy of sandstone before the peak stress was as follows 22 Inspired by the integral path independent of J integral, 23 the shear fracture energy of sandstone before the peak stress was as follows…”
Section: Shear Fracture Energymentioning
confidence: 99%
“…For instance, Sawai et al () demonstrate that decreasing effective pressure ( σn) causes a transition from stable to unstable slip behavior in blueschist samples. Ougier‐Simonin and Zhu (, ) also observed that shear localization in porous rocks could become unstable by decreasing effective pressure as pore pressure increases during the post failure stage of faulting. In addition, French et al () and Scuderi et al () show that fluid pressurization can overcome velocity‐strengthening friction to result in accelerated fault slip.…”
Section: Introductionmentioning
confidence: 96%
“…Увеличение объема порового пространства сопровождается резким падением локального порового давления. Известно, что неупругая деформация, как правило, носит локализованный характер и проявляется в виде узких полос локализованного сдвига (в геосредах такими макроскопическими полосами являются раз-ломные зоны) [8,15,19,36,39]. При этом прилегающие к полосам локализованного сдвига области материала или структурные блоки геосреды испытывают в основном упругую де-формацию.…”
Section: влияние жидкой фазы на прочность упругопластического слоя в unclassified
“…В рамках данной концепции ключевая роль в процессах зарождения землетрясений в активных разломных зонах, слагаемых проницаемыми мате-риалами, принадлежит жидкости. Важную роль при этом играет не только поровое давле-ние жидкости, но и ее перераспределение в разломной зоне и прилегающих объемах ок-ружающих блоков [34][35][36]. Как отмечено в ряде работ, наличие жидкости оказывает су-щественное влияние на землетрясения, приуроченные к разломам, в связи с тем, что дав-ление жидкости частично компенсирует нормальное давление в плоскости разлома, сни-жая тем самым его сдвиговую прочность [34,37,38].…”
unclassified